When sergeants can outrank generals: Person-organization fit and the performance of franchisees as agents of their franchisor - Semrau, Thorsten; Biemann, Torsten (Journal of Business Venturing, 2022)
We introduce a person-organization fit perspective to explain how franchise organization characteristics shape the link between franchisees' individual attributes and their performance as agents of their franchisor. Showcasing this idea, we develop arguments to suggest why the links between franchisees' agent performance and their prior industry and educational experiences are contingent upon the franchise organization's entrepreneurial orientation, centralization, and formalization. The results from multilevel analyses using the data of 276 franchisees from 47 franchise organizations largely support our ideas. We discuss the theoretical and practical implications of our study for franchising and beyond.